The Use of Discriminant Analysis for Assessing the Risk of Bankruptcy Among Polish Meat Processing Enterprises - Zielińska-Chmielewska, Anna (Studia Oeconomica Posnaniensia, 2015)
Bankrupt firms pose a significant problem to the proper functioning of every economy. Thus, bankruptcy prediction is becoming a more and more important issue from an economic point of view. The aim of this study was to assess the financial situation of selected meat processing enterprises with respect to their bankruptcy risk. In order to assess the financial condition of the enterprises examined, selected Polish models of discriminant analysis were used. The companies were selected for the study according to the following criteria: meat processing being the main area of business operations (companies belonging to group 15.11 according to the Polish Classification of Activities - PKD); a specific legal status (a limited liability company or a joint stock company employing more than 50 people); and the availability of financial data. The research shows that all the analysed meat processing companies were in a good financial condition, with the exception of Pamapol and Tarczyński which experienced financial difficulties in the period 2008-2009. The highest prognostic levels of bankruptcy were shown by D. Wierzba's model (for all the examined enterprises), the INE PAN 6 model (DUDA SA in 2009), the INE PAN 7 model (DUDA SA in 2009 and Pamapol SA in 2008), and D. Hadasik's model (Pamapol SA in 2008-2009).